Резонансные методы определения трикритических точек в тетрагональных антиферромагнетиках - Завражная, Е.М.; Медведовская, О. Г.; Чепурных, Г.К. (Видавничий дім "Академперіодика" НАН України, 2008)
Methods of experimental construction of magnetic phase diagrams by means of a dielectric resonance are proved. For this purpose, the behaviour of components of the static magnetic susceptibility tensor in the vicinities of three-critical points on the lines of phase transitions of the first and second kinds is determined.